Improving Online Marketing and the Role of Local Influencers in Riau Province, Indonesia - Eka Putra (Jurnal Riset Komunikasi (JURKOM), 2025)
This research explores the role of local influencers in online marketing in Riau Province, focusing on four key aspects: popularity, credibility, attractiveness, and power as contained in The Meaning Transfer Model theory. Influencers have great potential to attract consumer attention through interesting content. The credibility of an influencer is very important because consumers tend to trust their recommendations in product promotions. The visual appeal and personal interaction between influencers and followers creates a close relationship, increasing engagement and brand loyalty. Through Instagram, local influencers serve as a bridge between brands and audiences. This research uses qualitative methods by interviewing local Riau influencers about their experiences in marketing products that can provide added value to online marketing strategies. The results show that local influencer support positively impacts online marketing. These findings are expected to guide marketers in formulating more effective marketing strategies in the digital era.